Motivations for enrolling in university courses: Insights from an entrepreneurship course - Adolph C. Neethling (The Southern African Journal of Entrepreneurship and Small Business Management, 2024)
Background: Studies on the impact of entrepreneurship education (EE) have produced mixed results, leading researchers to examine the reason for such inconsistencies. This article examines course enrolment motivation, as a possible factor contributing to the inconsistency in findings on EE impact studies.